Analisis Maturasi Gigi pada Tikus yang Mengkonsumsi Minyak - Didin Erma Indahyani (Pustaka Kesehatan, 2014)
Dental maturation is a process of anorganic mineral apotition and resorption ofprotein and water content in the matrix of teeth during the stage of growth and developoment.Disturbances in the stage will caused abnormalities of tooth e.i. hypoplasia andhypomineralisation that are known tooth hypomaturation. The disorder may be systemic orlocal, because of trauma, infection, hormonal, systemic diseases, nutritional deficiencies, etc.fish oil of lemuru containing Eicosanoid acid (EPA) and docohexanoic acid (DHA) are highenough. The EPA and DHA are antiinflammatory and play a role in the regulation ofsignaling molecules and imunomudulator. The purpose of this study was to analyze thematuration of teeth in rats consuming fish oil of lemuru after periodontal infection induced byLPS during amelogenesis. 30 male Wistar rats aged 5 days, divided into three groups. Thefirst group was rats induced by lypopolisacharide (LPS) in the molar region (it aims to makedental maturation disorder). The second group was rats inducted LPS and given fish oil, andthe third group was not LPS induction and not given fish oil (normal). After the rats is agesof 21 days, were done decaputation. Upper right molar teeth have been taken to doobservation in macroscopic (clinical) and microscopic (SEM). Microscopic andmacroscopic observations done scoring, and statistically analyzed using one-way ANOVAand LSD. The results of this study showed that significantly (p <0.005) rats fed fish oil oflemuru, maturation teeth better than LPS-induced rats. It was concluded that fish oil affectsthe maturation lemuru rat teeth, and prevent tooth maturation disorder is more severe.Key words : fish oil, tooth maturation, amelogenesis, SEM